2020
DOI: 10.1007/s42452-020-2367-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of a footing adjacent to dynamically loaded footing on gypseous soil

Abstract: This paper presents an experimental study on the dynamic response of a circular foundation, underneath the have an impact on of a dynamic load that outcomes from the placement of a neighbouring footing said as (vibration source), having square-shaped and excited by way of a known source of vibration placed on top of it. The cause is to evaluate the effect of dynamic motion closely by group called the second foundation. Both foundations were founded on collapsible soil (gypseous soil) with a content of gypsum 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The findings demonstrated that both second baseline's acceleration and amplitude decreased as the interval between inspirations widened. Additionally, these factors had a higher value in a dry state than in a wet state [12]. Ling et al (2021) used a dynamically effective finite element to investigate the effects of the frequency content of the input motion and the amplitude of both the horizontal and vertical components of the input motion on pile settlement in saturated sand sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The findings demonstrated that both second baseline's acceleration and amplitude decreased as the interval between inspirations widened. Additionally, these factors had a higher value in a dry state than in a wet state [12]. Ling et al (2021) used a dynamically effective finite element to investigate the effects of the frequency content of the input motion and the amplitude of both the horizontal and vertical components of the input motion on pile settlement in saturated sand sediments.…”
Section: Introductionmentioning
confidence: 99%